Spatial Ability and Theory of Mind: A Mediating Role of Visual Perspective Taking. Issue 4 (28th January 2021) - Tian, Mi; Luo, Tianrui; Ding, Jinxia; Wang, Xin; Cheung, Him
Abstract : This research tests the role of visual perspective taking (VPT) in mediating the relation between spatial ability and theory of mind (ToM). Study 1 demonstrated such mediation correlationally in seventy 3.5‐ to 4‐year olds. In Study 2, twenty‐three 3.5‐ to 4‐year‐olds were trained on using play blocks to copy preassembled models as a way to promote spatial ability. Resultant increases in VPT and ToM were compared to those from a control group learning to draw instead ( n  = 23). Both studies showed that the effect of spatial ability on ToM depended on VPT, suggesting a role of embodiment in ToM development in early childhood. These findings provide an alternative way to think about ToM development and the psychological mechanism that may be involved.